ANALISIS KINERJA TEMPAT PEMBUANGAN SAMPAH (TPA) SUWUNG - Konsukartha, IGM.; Diana Harmayani, Kadek (Jurnal Ilmiah Teknik Sipil, 2012)
Population growth accompanied by high urbanization rate to Denpasar City and Badung Regency, as the center of commerce and tourism, caused increased amount of municipal solid waste. Government of Denpasar municipality and Badung regency solved the problem by constructing final dumping sites in Suwung. Implementation of performance analysis of Suwung final dumping sites was needed to decrease negative impact to social culture and social economic of the comunity around Suwung and to get an environment friendly management system. The method used is descriptive qualitative, use scoring system in its data processing. The input was primary and secondary data. Secondary data were obtained from DKP and monography were obtained from the offices of the heads of the villages, whereas primary data were obtained via questioner, field observation and depth interview. Social culture and social economic analysis were obtained by questioner and infrastructure and human resources analysis were done by field observation and depth interview. The data from questioner, field observation and depth interview were analysed and valued. The values given determine the level of performance of each component. The performance of the infrastructure of Suwung final dumping sites was categorized very bad (1.23), which shows that the current facilites did not function properly or did not function anymore. The performance of human resource was categorized at medium level (2.72), which shows that the workers did not perform their job and responsibility at their best. The result of evaluation of the impact to social culture aspect of the villages of Dukuh, Kawan, Pesanggaran and Suwung Batan Kendal as settlement area was categorized at medium level (3.10), which showed that the people surrounding the dumping sites were not disturbed in doing their tradition activities, although the smell was still disturbing. Evaluation of impact to social economic aspect of the four villages showed medium category (3.28), which means that Suwung final dumping sites did not affect the income of the communities. But nevertheless it open up work opportunity to the people that make use of it.
Keywords: final dumping sites, infrastructure, human resources, social culture, social economic